Lesch-nyhan syndrome in an Indian child - Priyanka Chandekar; Bhushan Madke; Sumit Kar; Nidhi Yadav (Wolters Kluwer Medknow Publications, 2015)
Hypoxanthine guanine phosphoribosyl transferase-1 (HGPRT-1) leading to Lesch-Nyhan syndrome (LNS) is one of the important causes of self-mutilation. Hereby, we report a case of LNS in a three and half-year-old male child, who presented with characteristic self-mutilating behavior. He had history of developmental delay, difficulty in social interaction, attention deficit and features of autism. His serum blood biochemistry was normal except for low hemoglobin levels and raised serum uric acid levels. With a diagnosis of LNS, the child was treated with allopurinol. With various modalities of physical restraint, his self-mutilating behavior came under control and currently the patient is being followed up.